OPINI AUDIT GOING CONCERN SERTA DETERMINAN YANG MEMPENGARUHINYA - Veronika, Agnes; Wardini, Anggi Putri Kusuma; Suryo, Medianto; Setiawan, Audita (Jurnal SIKAP (Sistem Informasi, Keuangan, Auditing Dan Perpajakan), 2024)
This study aims to examine and analyze the factors influencing the acceptance of a going concern audit opinion, focusing on firm size, financial condition, debt to total assets ratio, and debt to equity ratio. The research sample consists of 19 companies in the textile and garment sub-sector listed on the Indonesia Stock Exchange (IDX) during the 2019–2021 period. Secondary data were utilized and analyzed using logistic regression with IBM SPSS Statistics version 26. The findings indicate that financial condition and debt to total assets ratio have a significant effect on the likelihood of receiving a going concern audit opinion. In contrast, firm size and debt to equity ratio do not have a statistically significant impact on the issuance of such an opinion.